An analysis of the SME–bank match made in heaven: the case of New Zealand main banks and their relationship-managed SMEs. (17th June 2020) - Boulanouar, Zakaria; Locke, Stuart; Holmes, Mark
Abstract : Purpose: The purpose of this paper is to answer the increasing calls to analyse how lending relationship between banks and their small- and medium-sized enterprises (SMEs) work. More precisely, the main aim is to investigate the lending approach(es) and criteria used by banks to assess loan applications from their relationship-managed (RM) SMEs' clients. Other objectives include investigating the level of congruence in terms of lending practices and processes among the sample banks in New Zealand (NZ) and to discern how the assessment of the SME owner/manager is done within the relationship-banking framework. Design/methodology/approach: The research objectives concern investigating processes and not variances. Thus, a qualitative research approach was used. Extensive data was collected via interviews across representative banks in NZ and thematic analysis was used to analyse the data. Findings: The findings include a detailed analysis of how relationship banking actually works; how in NZ, the main bank brands use three criteria of lending (financials, security and character) as a framework of assessing loan applications from RM-clients – which is different from the character, capital, capacity, conditions, and collateral (5Cs) that are widely used and discussed as the framework of lending; and an elucidation as to why and how character assessment is different from the other criteria of lending. Originality/value: To the best of authors' knowledge, this is the first study to investigate the mechanisms and processes that banks use to deal with their RM-SMEs, show the existence of a different framework of lending other than the 5Cs and attempt an explanation as to why character evaluation is different from that of the other criteria of lending.